Molecular typing of Salmonella Typhimurium isolates using repetitive sequence- based PCR: Insights into genetic relatedness beyond antibiotic resistance - V, KUMAR SIVA; MAANSI; M, KUMAR SUMAN; A K, UPADHYAY (The Indian Journal of Animal Sciences, 2025)
Multidrug resistant non-typhoidal Salmonella infections are a threat to food safety impacting human health in the form of hospitalizations and in severe cases, fatalities. Epidemiological investigations of an outbreak require accurate identification of the infection source and the transmission route for effective implementation of preventive measures against microbial food-borne pathogens. Therefore, the present study investigates the repetitive sequence-based PCR (rep-PCR) fingerprinting techniques for genotyping of multidrug-resistant isolates of Salmonella Typhimurium. ERIC, REP, BOX and GTG5-PCR fingerprinting generated reproducible band patterns ranging from 3-10, 1-5, 6-14 and 2-10 separate bands, respectively. Cluster analysis revealed 9 types from ERIC-PCR, 7 types from REP-PCR, 16 types from BOXPCR and 9 types from GTG5-PCR. Hundred percent typeability was obtained with all genotyping techniques except REP-PCR. The isolates’ sharing similar band patterns is suggestive of genetic relatedness pointing towards the multifactorial involvement in the transmission of Salmonella. Faecal isolates and meat swab isolates sharing identical band patterns and grouped into a single cluster is indicative of a likely cross contamination. No unique pattern was observed in penta resistant (ACSSuT) profile isolates by our typing techniques. Discrimination index (DI) value of BOX-PCR was highest (0.940) followed by GTG5-PCR (0.862), REP-PCR (0.846) and ERIC- PCR (0.843). On comparing the techniques, the BOX-PCR exhibited good DI value, typeability and complex band pattern on gel in differentiating the isolates. Conclusively, the BOX-PCR fingerprinting technique was found useful in the genotyping of isolates thus suitable enough to find its application in an epidemiological investigation during an outbreak.